Analisis Isi Surat dan Pengulangan Kalimat pada Terjemahan Al-Qur'an Surat Ar-Rahman dan Implementasinya Sebagai Bahan Ajar - Aprilingtyas, Indri Nur; , Prof. Dr. Markhamah, M.Hum (2016)
Abstract Learning Indonesian generally study analyzes the various forms of sentences. Good level of junior high school and high school / vocational content analysis would have studied the readings, sentences, novels, and short stories. In SK and KD are learning about analyzing the content of the sentence, reading, novels, and short stories. In a passage contained the contents of the reading. In terms of content is analyzed in order to know what is contained on a bacaa it. However, in this study will analyze the translation of the Qur'an Surat ar-Rahman paragraph (1) - (78). This study aimed to analyze the contents of the letter and the repetition of the phrase contained in the translation of the Qur'an Surat ar-Rahman. This research was descriptive qualitative. The research data is a translation of the Qur'an Surat ar-Rahman paragraph (1) - (78). Menggunakanan data analysis methods of data analysis techniques. This method is done by reading and understanding the translation of verses of the Qur'an. Furthermore, analyzing the contents of the translation of the Qur'an Surat ar-Rahman and analyze repetitions sentence on translation of the Qur'an Surat ar-Rahman contained in each verse. The results of this study indicate that there are 31 repetition of the sentence contained in the translation of the Qur'an Surat ar-Rahman. Based on the contents of the letter Ar-Rahman mentioned qualities of God is God's merciful nature contained in paragraph (1), and (78). Both the nature of God is (form) contained in paragraph (3), (14), and (15). God knows the nature of (science) contained in paragraph (33), (35), (41), and (43). Eternal nature (baqa) contained in paragraph (26) and (27). Nature view (bazaar) contained in paragraph (64), (66), (68), (70), (72), (74), and (76). The nature of the ruling (qudrat) contained in paragraph 78. The nature of wills (Iradat) contained in paragraph (1), (2), (3) and (4). Stand-alone nature of God contained in paragraph (6), (7), (10), and (29). God is paying attention contained in paragraph (31). In addition to the findings of several attributes of God are also the repetition of the phrase contained in the translation of the Qur'an Surat ar-Rahman is on the favors of Allah. God favors human creation contained in paragraph (14) - (16) Allah's favor on two seas that meet, but remain split contained in paragraph (17) - (21), the favor of God about the decline of pearl and Marjan contained in paragraph (22) - (23), delights of the greatness of God contained in paragraph (24) - (25), the favor of God upon the greatness and glory that was revealed to mankind contained in paragraph (26) - (28) Allah's favor on time contained in subsection (29 ) - (30), delights of the attention and power of God contained in paragraph (31) - (45), delights God of heaven contained in paragraph (46) - (77), God favors the owners of grandeur and glory contained in paragraph (78 ).